2021
DOI: 10.1609/aaai.v35i17.17841
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to Machine Learning with Robots and Playful Learning

Abstract: Inspired by explanations of machine learning concepts in children’s books, we developed an approach to introduce supervised, unsupervised, and reinforcement learning using a block-based programming language in combination with the benefits of educational robotics. Instead of using blocks as high-end APIs to access AI cloud services or to reproduce the machine learning algorithms, we use them as a means to put the student “in the algorithm’s shoes.” We adapt the training of neural networks, Q-learning, and k-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…The discussion around physical and virtual ER platforms is not new [18,45] and has been given new impetus by the constraints imposed by COVID-19 [44,46]. Olary et al [47] used a virtual ER platform to explore the introduction to machine learning with 24 children. Ketterl et al [48] reported on the potential identified over the years by the German initiative Roberta-Learning With Robots, an online platform for visual programming of educational robots.…”
Section: Educational Roboticsmentioning
confidence: 99%
“…The discussion around physical and virtual ER platforms is not new [18,45] and has been given new impetus by the constraints imposed by COVID-19 [44,46]. Olary et al [47] used a virtual ER platform to explore the introduction to machine learning with 24 children. Ketterl et al [48] reported on the potential identified over the years by the German initiative Roberta-Learning With Robots, an online platform for visual programming of educational robots.…”
Section: Educational Roboticsmentioning
confidence: 99%
“…Alguns estudos tem levantado a perspectiva de aprendizagem por parte dos robôs no âmbito da RE (GUBENKO et al, 2021;LLOYD GREENWALD et al, 2006;OLARI;CVEJOSKI;EIDE, 2021). O conhecimento sobre como as máquinas aprendem é inspirado em certa medida na própria forma em como os seres vivos aprendem.…”
Section: Re Como Teoria De Aprendizagemunclassified
“…Alguns estudos tem levantado a perspectiva de aprendizagem por parte dos robôs no âmbito da RE (GUBENKO et al, 2021;LLOYD GREENWALD et al, 2006;OLARI;CVEJOSKI;EIDE, 2021). O conhecimento sobre como as máquinas aprendem é inspirado em certa medida na própria forma em como os seres vivos aprendem.…”
Section: Re Como Teoria De Aprendizagemunclassified